The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.jasms.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for structural variants of a- and b-type peptide fragment ions using combined ion mobility/mass spectrometry

Abstract: Tandem mass spectrometry (MS/MS) of peptides plays a key role in the field of proteomics, and an understanding of the fragmentation mechanisms involved is vital for data interpretation. Not all the fragment ions observed by low-energy collision-induced dissociation of protonated peptides are readily explained by the generally accepted structures for a-and b-ions. The possibility of a macrocyclic structure for b-type ions has been recently proposed. In this study, we have undertaken investigations of linear pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
66
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 13 publications
6
66
0
Order By: Relevance
“…), the "scrambling" of b-type ions would seem unlikely because the increase in size, conformational space that can be accessed, and degrees of freedom would make formation of the macrocycle entropically disfavored. However, the results of the study clearly establish the loss of sequence and are consistent with earlier reports of sequence scrambling for the larger b ions and are for b 5 ϩ [16,20] and larger b-type ions [17]. We note that the apparent scrambled b n ions do not contribute significantly to the product ion distribution(s) generated from the respective protonated precursor peptides (spectra not shown), thus suggesting that the influence of the cyclization reactions in the interpretation of CID patterns from (M ϩ H) ϩ may be minimal.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…), the "scrambling" of b-type ions would seem unlikely because the increase in size, conformational space that can be accessed, and degrees of freedom would make formation of the macrocycle entropically disfavored. However, the results of the study clearly establish the loss of sequence and are consistent with earlier reports of sequence scrambling for the larger b ions and are for b 5 ϩ [16,20] and larger b-type ions [17]. We note that the apparent scrambled b n ions do not contribute significantly to the product ion distribution(s) generated from the respective protonated precursor peptides (spectra not shown), thus suggesting that the influence of the cyclization reactions in the interpretation of CID patterns from (M ϩ H) ϩ may be minimal.…”
Section: Discussionsupporting
confidence: 91%
“…However, recent experiments [16,17] suggest that cyclization of the linear, oxazolone-terminated b ions can occur to generate a macrocyclic b ion isomer, which can then open at several different amide bonds to re-form linear, oxazolone-terminated ions with concomitant scrambling of the original primary sequence (Scheme 1). We refer to this type of process as b-type scrambling of peptide fragment ions [16].…”
mentioning
confidence: 99%
“…In a recent paper, Harrison and coworkers [20] proposed that oxazolone terminated linear b ions can cyclize by nucleophilic attack of the N-terminal amino group on the charged oxazolone ring. This reaction leads to a macro-cyclic b isomer [21], the existence of which has recently been demonstrated by Gaskell and coworkers [22] using ion mobility spectroscopy. Cyclic b ion structures can in principle open up at any amide bond (b-type scrambling) and this reaction can lead to linear isomers with scrambled primary structures.…”
mentioning
confidence: 80%
“…Quantum chemical calculations indicated that the cyclic form is energetically more favored than the linear structures. Ion mobility experiments [22,31] confirmed that a ions have multiple structures. A recent CID and theoretical study [32] from our laboratories indicated that the CID spectra of a 5 fragments of YAGFL-NH 2 can reasonably be understood by assuming an interplay of b-type scrambling [20] of the corresponding b parent population and a ¡ a* type rearrangements [30].…”
mentioning
confidence: 85%
“…After many years of characterization by MS/MS, the study of isomeric gas-phase ion structures has been recently the domain of ion mobility-mass spectrometry (IM-MS) and action IRMPD spectroscopy. Gaskell and coworkers used IM-MS to identify both oxazolone and macrocyclic structures for the b 5 ion from YAGFL-NH 2 , while Clemmer and coworkers used a similar approach to identify linear and macrocyclic structures for the a 4 and b 4 fragment ions from leucine enkephalin [21,22]. Variable wavelength action IRMPD spectroscopy has been recently employed by several research groups for the study of gas-phase ions [23][24][25][26] and has also been the subject of two recent, extensive reviews [27,28].…”
mentioning
confidence: 99%